Does China's middle class prefer (liberal) democracy?. Issue 2 (23rd February 2017) - Wu, Wen-Chin; Chang, Yu-Tzung; Pan, Hsin-Hsin
ABSTRACT: Many surveys show that China's political regime, under the Chinese Communist Party's authoritarian rules, enjoys a high level of public support. However, it is still uncertain whether China's emerging middle class will become the "agent of democratization" as suggested by modernization theory. Using the data of Asian Barometer Survey conducted in China in 2011, this article demonstrates that the relationship between class identity and preference for liberal democracy in China may be inverted U-shaped. The Chinese middle class shows a higher preference to features of liberal democratic regimes than its counterparts of the lower- and upper-class. Members of the Chinese middle class also tend to regard democracy as the best form of government. Thus, the middle class has the potential to initiate democratization in China if the Chinese government fails to keep satisfying the middle class' quest for economic well-being and protection of property rights.